2002
DOI: 10.1073/pnas.152101299
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell imaging reveals divergent intracellular dynamics of polyglutamine disease proteins and supports a sequestration model of pathogenesis

Abstract: Protein misfolding and aggregation are central features of the polyglutamine neurodegenerative disorders, but the dynamic properties of expanded polyglutamine proteins are poorly understood. Here, we use fluorescence recovery after photobleaching (FRAP) and fluorescence loss in photobleaching (FLIP) with green fluorescent protein fusion proteins to study polyglutamine protein kinetics in living cells. Our results reveal markedly divergent mobility states for an expanded polyglutamine protein, ataxin-3, and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 41 publications
10
138
3
1
Order By: Relevance
“…5). This result is consistent with previous reports that the GFP fluorescence of polyglutamine protein aggregates is not recovered after photobleaching (36,37). These findings indicate that dot-like accumulations of mutant ␥PKC-GFP are indeed aggregates, but are not the simple result of targeting to particular cell organelles.…”
Section: Discussionsupporting
confidence: 93%
“…5). This result is consistent with previous reports that the GFP fluorescence of polyglutamine protein aggregates is not recovered after photobleaching (36,37). These findings indicate that dot-like accumulations of mutant ␥PKC-GFP are indeed aggregates, but are not the simple result of targeting to particular cell organelles.…”
Section: Discussionsupporting
confidence: 93%
“…Similar dynamic mobility is exhibited by aggregates of poly-Q expanded ataxin-1 molecules (Stenoien et al, 2002). Both contrast with the behavior of aggregates of poly-Q expanded ataxin-3 that are largely immobile and do not exchange their components (Chai et al, 2002). These results indicate that structures defined morphologically as visible inclusions can be true aggregates (as those formed by ataxin-3) or concentrated depositions of rapidly exchanging components (as those formed by ataxin-1 and GFP170*).…”
Section: Deposition Of Nuclear Aggregates By Nonpoly-q Gfp170*mentioning
confidence: 72%
“…The t 1/2 of fluorescence recovery to steady state levels is ϳ50 s. The recovery of GFP170* is slower than that of a poly-Q expanded GFP-ataxin-1-84Q (t 1/2 of Ͻ2 s) deposited in nuclear inclusions of similar size (Stenoien et al, 2002). However, GFP170* recovers significantly faster than the almost immobile poly-Q expanded ataxin-3 (Chai et al, 2002) or Q82-GFP (Kim et al, 2002). To provide a direct comparison between dynamics of GFP170* and an immobile aggregate, we analyzed FRAP of Q82-GFP.…”
Section: Cytoplasmic and Nuclear Gfp170* Aggresomes Are Dynamicmentioning
confidence: 95%
“…Several studies have convincingly demonstrated that the interaction of polyQ-expanded htt proteins with other Q-rich proteins correlates with toxicity in mammalian cells (14,24,25). Because all of the previously studied Q-rich proteins are essential, their sequestration into polyQ aggregates, and the ensuing loss of their function could well have been the sole mechanism accounting for toxicity (26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%